2017
DOI: 10.1186/s11671-017-1861-y
|View full text |Cite
|
Sign up to set email alerts
|

Plant Response to Engineered Metal Oxide Nanoparticles

Abstract: All metal oxide nanoparticles influence the growth and development of plants. They generally enhance or reduce seed germination, shoot/root growth, biomass production and physiological and biochemical activities. Some plant species have not shown any physiological change, although significant variations in antioxidant enzyme activity and upregulation of heat shock protein have been observed. Plants have evolved antioxidant defence mechanism which involves enzymatic as well as non-enzymatic components to preven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
55
1
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 218 publications
(74 citation statements)
references
References 186 publications
4
55
1
4
Order By: Relevance
“…The plant defense mechanism is activated in response to stress, and increased amounts of protective enzymes and antioxidants are synthesized, such as ascorbate peroxidase, catalase (CAT), and superoxide dismutase (SOD). Studies have shown that nanomaterials influence plant growth and development via the ROS pathway [9]. Research has shown that under stress conditions, plant growth and defense responses are regulated in a coordinated manner by the activity of several phytohormones, such as ABA, CTK, GA and IAA.…”
Section: Introductionmentioning
confidence: 99%
“…The plant defense mechanism is activated in response to stress, and increased amounts of protective enzymes and antioxidants are synthesized, such as ascorbate peroxidase, catalase (CAT), and superoxide dismutase (SOD). Studies have shown that nanomaterials influence plant growth and development via the ROS pathway [9]. Research has shown that under stress conditions, plant growth and defense responses are regulated in a coordinated manner by the activity of several phytohormones, such as ABA, CTK, GA and IAA.…”
Section: Introductionmentioning
confidence: 99%
“…Metal oxide nanoparticles, which form a bulk of engineered nanomaterials, have been well studied under the purview of plant uptake [227]. Metal oxides like titanium dioxide, silver oxide, iron oxide, copper oxide and metal nanoparticles have been shown to accumulate in a variety of food crops and have even been detected in commercial produce [228][229][230][231][232]. A recent review by Ma et al describes studies of nanoparticle uptake by crops and their occurrence in the final produce [40].…”
Section: Engineered Nanomaterialsmentioning
confidence: 99%
“…These mechanisms consist of both non-enzymatic antioxidants, including the low molecular weight compounds (phenolics, ascorbate, a-tocopherols, glutathione, carotenoids, and proline), and enzymes such as superoxide dismutase (SOD), catalase (CAT), peroxidase (POD), and ascorbate peroxidase (APX), among others (Getnet et al, 2015;Ozyigit et al, 2016). These antioxidants reduce ENP related oxidative injury in plants (Siddiqi and Husen, 2017). MDA is one of the by-products of oxidative stress and ROS that results from the oxidation of unsaturated fatty acids on the cell membrane (Gaschler and Stockwell, 2017).…”
Section: Introductionmentioning
confidence: 99%